Study on knowledge, practices, and attitudes toward decentralized clinical trials among the clinical trial practitioners in China - Shi, Yuanyuan; Bao, Yujian; Pu, Yu; Jiang, Junhao; Yan, Bo; Zheng, Hang (Frontiers in Medicine, 2025)
BackgroundStudies on the application of decentralized clinical trials (DCTs) in China are limited. This study aimed to investigate the knowledge, practices, and attitudes of clinical trial practitioners in China toward DCTs.MethodAn anonymous cross-sectional study was conducted from November 1st to November 30th, 2023. A total of 621 valid questionnaires were collected, including 227 completed by Clinical Research Associates (CRAs), 150 by Clinical Research Coordinators (CRCs), and 244 by Program Managers (PMs).ResultsThe majority of respondents possessed basic knowledge of DCTs and showed a high willingness to participate, but their practice experience was limited, with a relatively high level of practice experience in internet recruitment. Respondents were more interested in the improvement of patients’ rights brought by DCTs, such as more opportunities for clinical trials. Technical barriers and data reliability were the main barriers to implementation.ConclusionClinical trial practitioners need to enhance their technical skills and knowledge about DCTs, enhance the overall level of the industry, and promote the better implementation and application of DCTs in China.